470 Evaluation of cardiovascular risk factor control among people with diabetes in the community pharmacy setting – a cross sectional study. (13th April 2023) - Zaki, M; O'Sullivan, C; Barrett, E; Thornton, H; Mirzai, N; Bermingham, M
Abstract: Introduction: Diabetes affects almost 140, 000 Irish people and the prevalence is increasing.(1) In Ireland there is no structured programme in place for community pharmacists to provide care to people with diabetes, outside of dispensing medications and supplying medical devices. Research shows that community pharmacists can provide advanced services to people with diabetes that improve glycaemic control, cardiovascular risk, and medication profile.(2) A pharmacist-led intervention among people with diabetes in the Irish community pharmacy setting may be beneficial in addressing these treatment goals. However, baseline data to support this is not available. Aim: To assess the cardiovascular risk profile of people with diabetes attending community pharmacy in Ireland. Methods: This was a cross-sectional study. Data collection took place in 10 pharmacies, identified by purposeful sampling, in four Irish counties, and was conducted by five pharmacy students. Data collection in each pharmacy lasted between five and six weeks and took place between July 2018 and October 2019. A target sample size was not set. Study participants were aged 18 years and older, with type 1 or type 2 diabetes, attending a participating pharmacy and to whom oral diabetes medicines, insulin or devices for monitoring glycaemic control were dispensed. A data collection form was designed for the study, based on the RxEACH study.(2) Participants were asked their demographics, medical history, and cardiovascular risk factors. Current medications were identified using dispensing software. Data were presented as mean±standard deviation or number (%). Data were analysed in SPSS v28. Results: Data were available for 106 participants, 70 (66.0%) male, mean age 63.5±13.7 years. Of these, 90 (84.9%) had type 2 diabetes and 16 (15.1%) had type 1 diabetes. Hypertension and dyslipidaemia were reported by 60 (56.6%) and 59 (55.7%) participants, respectively. This was followed by family history of premature heart disease (N=40, 37.7%), coronary artery disease (N=10, 9.4%), and atrial fibrillation (N=9, 8.5%). Twenty-one participants (19.8%) were current smokers, 31 (29.2%) followed no specific diet, and 44 (41.5%) did not undertake exercise. Oral diabetes medication was prescribed to 85 (80.2%) participants and insulin to 29 (27.4%) participants. Antihypertensive medication was prescribed to 67 (63.2%), lipid-lowering therapy to 53 (50.0%) and an antiplatelet agent to 51 (48.1%) participants. Participants reported that they received education about diabetes medicines from their general practitioner (N=49, 46.2%), endocrinologist (N=21, 19.8%), diabetes nurse (N=28, 26.4%), dietician (N=3, 2.8%), pharmacist (N=17, 16.0%), other source (N=17, 16.0%). Twelve (11.3%) participants reported never receiving medication education. Conclusion: Study limitations include being confined to a small number of pharmacies in a geographically limited area and that medical history was based on self-report. Strengths include the use of a robust method of collecting medication data. People with diabetes attending study pharmacies had high rates of behaviours associated with cardiovascular risk including smoking and lack of exercise. Fewer than one-in-six participants reported receiving diabetes medication education from their pharmacist. Pharmacist-led interventions to engage people with diabetes in discussing health behaviours and medication education should be developed and explored as potential future professional services delivered by Irish pharmacists. References: 1. International Diabetes Federation. International Diabetes Federation Diabetes Atlas: Ireland. Accessed: Nov. 30, 2022. [Online]. Available: https://diabetesatlas.org/data/en/country/97/ie.Html 2. Al Hamarneh YN, Hemmelgarn BR, Hassan I, Jones CA, Tsuyuki RT. The effectiveness of pharmacist interventions on cardiovascular risk in adult patients with type 2 diabetes: the multicentre randomized controlled RxEACH trial. Can J Diabetes. 2017;41(6):580–6.